(untitled) (Journal of Informatics Education and Research, 2025)
Low-income households in India should get educated on finances and create financial stability since they regularly have major economic problems and might encounter unpredictable situations. Throughout the paper, it is examined how better financial education gives these families the ability to cope with sudden expenses related to healthcare or an income reduction. The research explores basic aspects of understanding finance, resilience, the problems low-income families face in gaining financial education and looks at the available initiatives from federal and community sources to support improving financial education. The research considers how low-income households in India differ socio-economically and explores how they use their understanding of financial matters to make good decisions about savings, investments and debts. The results of this research indicate that poor families receive strong shock resistance thanks to financial literacy, yet there are still major issues in getting this knowledge to them through education programs. The paper ends by outlining policy improvements as well as developing new methods to support financial knowledge and security for poor communities in India.